Reliability and validity study of the Spanish adaptation of the "Student Satisfaction and Self-Confidence in Learning Scale" (SCLS). - Mariona Farrés-Tarafa (Public Library of Science (PLoS), 2021)
The European Higher Education Area (EHEA) recommends the use of new educational methodologies and the evaluation of student satisfaction. Different instruments have been developed in Spain to evaluate different aspects such as clinical decisions and teamwork, however no instruments have been found that specifically evaluate student self-confidence and satisfaction during clinical simulation. The aim was to translate the Student Satisfaction and Self-Confidence in Learning Scale (SCLS) questionnaire into Spanish and analyse its reliability and validity and understand the level of satisfaction and self-confidence of nursing students with respect to learning in clinical simulations. The study was carried out in two phases: (1) adaptation of the questionnaire into Spanish. (2) Cross-sectional study in a sample of 489 nursing students. The reliability and exploratory and confirmatory factorial analyses were performed. To analyse the relationship of the scale scores with the socio-demographic variables, the Fisher Student T-test or the ANOVA was used. The scale demonstrated high internal consistency reliability for the total scale and each of its dimensions. Cronbach's alpha was 0.88 (0.83 to 0.81) for each of the dimensions. The exploratory and confirmatory factor analysis showed that both the one-dimensional and two-dimensional models were acceptable. The results showed average scores above 4 for both dimensions. The SCLS-Spanish translation demonstrated evidence of its validity and reliability for use to understand the level of satisfaction and self-confidence of nursing students in clinical simulation. Clinical simulations help students to increase their levels of confidence and satisfaction, enabling them to face real scenarios in clinical practice.